ANALISIS FAKTOR INSECURE DAN IMPLIKASINYA TERHADAP TINGKAT KEPERCAYAAN DIRI SISWA DI SMP DAARU SHOFWAH - Utami, Alni Nur; Kasman, Rusdi (UIN Sumatera Utara Medan, 2025)
Insecurity is a psychological condition that can significantly hinder the development of self-confidence. This study aims to examine the implications of insecurity on students’ self-confidence. Using a qualitative descriptive approach, data were collected through in-depth interviews with selected participants. The data analysis process involved selecting, focusing, simplifying, abstracting, and transforming the information obtained. The findings reveal that insecurity manifests in various forms, such as persistent feelings of inferiority, low self-esteem, constant self-comparison with others, and heightened awareness of personal shortcomings when observing others’ strengths. These conditions lead students to perceive others as more capable, more attractive, or more easily loved, which in turn diminishes their own sense of worth and self-confidence. The study highlights the need for targeted interventions to help students build a positive self-concept and overcome the negative effects of insecurity.